Multisystemic Resilience 2021
DOI: 10.1093/oso/9780190095888.003.0022
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Resilience in Response to Adverse Experiences

Abstract: In the field of developmental psychology, resilience is broadly understood as positive adaptation despite exposure to adversity. The concept provides an explanation for the wide variability in mental health outcomes observed in children exposed to adverse experiences. Although resilience has become an important and influential concept in the field, some fundamental questions remain, such as how it should be defined and operationalized and what the specific processes are that lead to positive mental health outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Previous research in refugee populations has identified a range of factors across individual and social systems that predict risk and resilience (Popham, McEwen, & Pluess, 2021; Scharpf et al., 2021). For example, different coping strategies show adaptive or maladaptive functions (Khamis, 2019a), while parenting can either buffer or exacerbate the impact of adversity on children's mental health (Bryant et al., 2018; Khamis, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in refugee populations has identified a range of factors across individual and social systems that predict risk and resilience (Popham, McEwen, & Pluess, 2021; Scharpf et al., 2021). For example, different coping strategies show adaptive or maladaptive functions (Khamis, 2019a), while parenting can either buffer or exacerbate the impact of adversity on children's mental health (Bryant et al., 2018; Khamis, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…manifested resilience; Miller-Graff 2020). However, the process of adapting to adversity can take different trajectories (Popham et al ., 2021). Children struggling at one timepoint may recover, while continuing accumulation of stressors may cause a child originally doing well to deteriorate (Müller et al ., 2019).…”
mentioning
confidence: 99%
“…In terms of mental health trajectories, the science of resilience has already clarified how modeling individuallevel health outcomes over time can help identify pathways to resilience, resistance, or posttraumatic growth; this is often done, however, with reference to acute-onset trauma such as a disaster or terrorist attack (Bonanno et al, 2015;Masten & Narayan, 2012). In protracted or post-conflict settings, pathways to mental health and resilience can be more complex to ascertain, due to the interplay of ongoing and past adversities (Betancourt et al, 2013;Tol et al, 2013), potential differences in environmental sensitivity affecting responses to war exposure (Popham et al, 2021), and developmental cascades across multiple, nested systems providing context to life-course experiences (Masten and Cicchetti, 2010). Recent work now pays careful attention to the role of family environments in examining changes in child mental health over time (Popham et al, 2022).…”
Section: Pathways To Resilience In Afghan Communitiesmentioning
confidence: 99%